A framework for workplace information literacy in academic contexts: Central University of Technology, Free State (South Africa) as case study. Issue 4 (16th November 2015) - Fourie, Ina; Molopyane, Jeannet
Abstract : Purpose: – The purpose of this paper is to suggest a framework for workplace information literacy based on a case study at the Central University of Technology (CUT), Free State (South Africa). Design/methodology/approach: – The framework is based on a literature survey covering case studies from the private, public and academic sector and a case study conducted at the CUT, Free State (South Africa). A mixed methods approach was followed using questionnaires, individual interviews and focus group interviews. Descriptive statistics and qualitative data were collected. Findings: – The data analysis reveals a need as well as support for workplace information literacy. It addresses institutional buy-in, the need for alignment to the institutional strategy, inclusion of workplace information literacy in job descriptions, whether workplace information literacy should be optional or mandatory, whether it should address the needs of all staff members, the responsibility for a workplace information literacy programme, perceived benefits, etc. Practical implications: – The proposed framework can be used at the CUT, Free State. As a general framework it can also be used in other academic contexts as well as in the public and private sector. Originality/value: – Although several studies on workplace information literacy have been reported, the literature survey did not trace a suitable framework that can guide the design and implementation of workplace information literacy in academic contexts. This paper intends to contribute towards filling this gap.